2001
DOI: 10.1016/s1526-9523(00)00091-x
|View full text |Cite
|
Sign up to set email alerts
|

Serving Women in Need: Nurse‐midwifery Practice in the United States

Abstract: Study results, taken in conjunction with research that documents the safety of nurse-midwifery practice, reinforce policy recommendations that support expanded access to nurse-midwifery services. Findings also indicate a need for further research in the areas of CNM workload and productivity in managed care settings and the association between CNM race and ethnicity and the race and ethnicity of their clients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…Midwives and physicians begin with their own set of learned assumptions about the nature of pregnancy, childbirth, and the maternal-fetal connection, and then proceed to perform prenatal care and nutritional counseling with a select group of clients or patients who themselves come with their own sets of beliefs and values. Midwives, and especially those who attend out-of-hospital deliveries, often find themselves serving a self-selected group of clients who are relatively motivated and often healthier to begin with than the population at large (Declercq, Paine, and Winter 1995;Declercq, Devries, et al 2001), though as home delivery grows in popularity, midwives report a rising rate of poor and disenfranchised women who are at higher risk psychosocially (Cheyney 2005;Declercq, Williams, et al 2001). Obstetricians serve a broader patient base that they see as struggling with "the typical American problems" of poor diet and low exercise levels.…”
Section: Downloaded By [University Of Liverpool] At 17:20 03 October mentioning
confidence: 99%
“…Midwives and physicians begin with their own set of learned assumptions about the nature of pregnancy, childbirth, and the maternal-fetal connection, and then proceed to perform prenatal care and nutritional counseling with a select group of clients or patients who themselves come with their own sets of beliefs and values. Midwives, and especially those who attend out-of-hospital deliveries, often find themselves serving a self-selected group of clients who are relatively motivated and often healthier to begin with than the population at large (Declercq, Paine, and Winter 1995;Declercq, Devries, et al 2001), though as home delivery grows in popularity, midwives report a rising rate of poor and disenfranchised women who are at higher risk psychosocially (Cheyney 2005;Declercq, Williams, et al 2001). Obstetricians serve a broader patient base that they see as struggling with "the typical American problems" of poor diet and low exercise levels.…”
Section: Downloaded By [University Of Liverpool] At 17:20 03 October mentioning
confidence: 99%
“…It is known that nurse-midwives provide substantial amounts of care to vulnerable and underserved populations in the United States (Declercq et al, 2001) and that care is known to have outcomes equal to or better than that of other obstetrical providers (MacDorman & Singh, 1998;Rosenblatt et al, 1997). Limited data are available, however, regarding the nature of nurse-midwifery practice settings as well as compensation for services.…”
mentioning
confidence: 99%
“…In addition, a recent review article on midwifery care showed that midwives serve a high proportion of disadvantaged populations, including adolescents, racial/ethnic minorities, Medicaid beneficiaries, and women who are less educated, unmarried, or residing in rural areas or health professional shortage areas 6 . A large proportion of payments (44%) for CNM care is from Medicaid, which tends to have lower reimbursement rates 41 . Compared with other obstetric providers (obstetricians/gynecologists and family physicians), CNMs are paid a lower salary and are unable to offset lower insurance reimbursement with higher paying procedures such as surgery, 17,18,36 limiting their ability to absorb large increases in malpractice premiums.…”
Section: Resultsmentioning
confidence: 99%